Lumbar microdiscectomy with the simply modified taylor retractor - Cetinkal, Ahmet (Annals of Medical Research, 2021)
Aim: To describe the modifications we made to the Taylor retractor (TR) used in routine spinal surgery and present the results of cases that underwent surgery with the modified TR. Materials and Methods: We made two basic modifications to the TR used in standard spinal surgery practice: reducing the size of the instrument and reshaping the blade part. The study included the cases in which we performed unilateral lumbar microdiscectomy (LM) at one level with standard and modified TR between January 2016 and August 2020. The preoperative and postoperative third-month low back pain and ODI scores were statistically analyzed. Results: The mean age of the 50 patients was 42 years, and the male/female ratio was 1.38. Except a skin infection in Group A, no other complication was seen. The mean follow-up period was 12 months. The length of incision was 28 mm in Group A and 17 mm in Group B. When the preoperative and postoperative third-month VAS and ODI scores were statistically analyzed in terms of low back pain, a significant difference was found (p<0.001). Conclusion: Microdiscectomy is a gold standard method in LDH surgery. TR is a practical and easily accessible surgical instrument in spinal surgery. Technological advances in optical systems have provided a significant reduction in normal tissue damage in LM. In addition, the modified TR we presented in this paper does not require a learning curve and can contribute to obtaining satisfactory results in terms of normal tissue damage and reducing postoperative low back pain complaints.